ECONOMIC RESEARCH OF WORKING CAPITAL - Myroshnyk, N. V.; Miniaiev, A. O. (Science and Transport Progress, 2006)
The concept of «working capital» has been determined. It has been established that in conditions of market economy for efficient management a formation of normative base is necessary, which will permit to carry out the control of resource and financial flows. This is needed for optimization of the stocks level and minimization of the working capital invested thereto. Peculiarities of the economic research point on the necessity of use of variable and constant potions of the working capital, and their expenses and returns can be classified as per the centres of responsibility. All these expenses are adjusted at a certain administrative level.